A Case Study Of Applying Systems Thinking In Malaysian Organizations By Triple H Consulting Sdn. Bhd - Pakdel, Sahar (2007)
Triple H specializes in helping clients solving complex problems.This research is the result of six months research on the learning styles, action learning and systems thinking and another six months of applying, training and testing tehem in Malaysian organizations.